La ‘Vetus Latina’ y la confrontación cultural entre paganos y cristianismo - Moreno Hernández, Antonio (Antigüedad y Cristianismo, 1990)
The Old Latin Versions of the Bible, called Vetus Latino, were one of the main points in the Pagan critique of the Christian doctrines. This Article analyses the arguments of the Pagan authors against Vetus Latina and the answers of the Christians from the second to the fith century A.D. It is possible to discern three arguments, all of them concerning linguistic problems: the short literary quality of Vetus Latina, because of the literalism in the translation technique; the social and cultural background of the Christians, which are considered illiterate persons with a vulgar language; and the textual pluralism, owing to the existence of different versions.